rebecca asked in Science & MathematicsMathematics · 8 months ago

# how to solve 6-2(5-4)?

Relevance
• 8 months ago

6-2(5-4)

=6 - 2(1)

=6 - 2

• 8 months ago

I mightbbe totally wrong but I would do 6-2 which is 4 and multiply that times 1 which is 5-4

• 8 months ago

6-2(5-4)

To solve, solve the one in parentheses first.

6-2(1) because 5-4 = 1 (perform multiplication)

6-2 because 2(1) = 2 (perform subtraction)

4 because 6-2 = 4

Lesson: PEMDAS

• Anonymous
8 months ago

the answer is 4 (use order of operations)

• 8 months ago

6 - 2(5-4) =

6 - 2(1) =

6 - 2 =

4.

• 8 months ago

its 4. 6 - 2x1. It's how they taught us in school.

Source(s): Common sense
• Como
Lv 7
8 months ago

-

6 - 2 x 1 = 4

• Anonymous
8 months ago

Do 5 - 4 inside the brackets first

multiply 2 by what is inside the brackets.

then subtract the above from 6

4 is what you should get.

• 8 months ago

6 - 2(5 - 4) = 6 - 2(1) = 6 - 2 = 4

• 8 months ago

4. Parenthesis goes first so 5-5 = 1. Then multiplication goes next so 2(1) = 2. Finally 6 - 2 = 4.